Hyperbasophilic immunoblasts in circulating blood in chronic inflammatory rheumatic and collagen diseases. Issue 5 (October 1975) - Delbarre, F; Le Gô, A; Kahan, A
Abstract : The number of large circulating hyperbasophilic mononuclear cells - referred to as hyperbasophilic immunoblasts (HBI)- is often increased in collagen disease and rheumatoid arthritis (RA) and grossly reflects the degree of disease activity. In contrast, in psoriatic arthropathy the percentage of (HBI) is within the normal range. HBI are mainly involved in immune reactions and may provide a valuable routine test for the assessment of the latter in disease states and for the predicition of relapse in chronic collagen diseases. Immunofluorescent techniques applied to samples from active autoimmune diseases have shown that a number of HBI are Ig-producing B-blasts. Moreover, in a few cases these intracytoplasmic immunoglobulins exhibited a rheumatoid factor-like activity, a finding which promises to yield additional information on the immunopathogenesis of RA.